A Mesoscale Meteorological Model of Modified Land Cover to the Effect of Urban Heat Island in Jakarta, Indonesia - Yopi Ilhamsyah (Graduate Program of Syiah Kuala University, 2012)
Abstract - A mesoscale meteorological model of modified land cover to the effect of urban heat island (UHI) in Jakarta was done. Although higher temperature in the city has been generally known, factors and issues that result in the increase of temperature particularly nighttime temperature over the city, however, are not well-understood. Jakarta, the capital of Indonesia, is encountering urbanization problems foremost. The increasing demand of housing as well as rapid development of sky crapper building, market places and highway diminishes the vegetation which in turn trap heat in the troposphere throughout the year, particularly during dry season on June-August. The fifth-generation mesoscale meteorological model (MM5) was employed in the study. The model involves medium range forecast planetary boundary layer (MRF PBL) scheme and land surface with two following parameters: i.e. roughness length over land and thermal inertia of land. These two parameters are chosen to enhance the characteristics of land surface. The simulation was carried out for 3 days on August 5-7, 2004 during dry season. The results showed that the simulation of surface temperature done by MM5 modified land cover described a good comparison to that of weather observation data. As a result, the effect of UHI was also well-observed during day-time. In addition, MM5 modified land cover simulation also illustrated a well-development of sea-breeze and country-breeze during mid-day and nighttime, respectively. However, long-term simulation is still required. Thus, daily diurnal cycles of air temperature and their differences can be well-observed in detail.